Incorporation of 32Pi into nucleotides, polyphosphates, and other acid-soluble compounds by Myxococcus xanthus during myxospore formation. - Maeba, P Y (1978)
When glycerol was used to induce myxospore formation in Myxococcu xanthus in the presence of 32Pi, the label was incorporated into a variety of acid-soluble compounds. Incorporation into ribonucleotides was approximately fivefold greater than in vegetative cells or noninducible mutants grown in glycerol. The label was also incorporated into some unknown compounds and material tentatively identified as guanosine tetraphosphate. Marked accumulation into polyphosphates, which were present mainly in culture supernatants, occurred relatively late during myxospore formation. The kinetics of accumulation of some of these compounds and their distribution into acid-soluble cell extracts and culture supernatants are described and compared with those in vegetative cells and noninducible mutants.